The Role of Teachers in Classroom Management to Increase Student Learning Motivation - Riska Terina Tria Ferlin; Putri; Khasbi Ainun Najib (Konsultan Jurnal Ilmiah Indonesia, 2025)
One of the importanr concepts in teaching in schools is classroom management. Based on the results of literature studies, effective learning can increase student’s motivation and enthusiasm for learning. This article provides general information about the definition of classroom, and important tips that teachers use to ensure that the learning process is successful. In addition, this article highlight the importance of school guidance to increase student’s motivation in learning and identify potential problems that may arise during the learning process. By understanding the principles of effective classroom management and implementing appropriate strategies, teachers can create a safe and healthy learning environment and help students become more motivated and respectful of others. This article uses a literature analysis method based on relevant sources.